MODEL PENINGKATAN KINERJA PENJUALAN MELALUI INTERPERSONAL SKILLS, SALESMANSHIP SKILLS DAN TECHNICAL SKILLS SALESPERSON - Winarto, Winarto (Politeknik Negeri Semarang, 2018)
Sales performance has significant role toward marketing performance of a company. Sales performance is constitutedfrom the resultan of salesperson performance in a company. The purpose of this research is to build sales management model in order to increase sales perfomance through promoting interpersonal skills, salesmanship and technical skills of salesperson. Questionnaire is used for collecting data from the salesperson. Multiple linier regression is used to analyze data. The results of this reseach show that interpersonal skills, salesmanships skills and technical skills of salesperson have positive impact toward sales perfomance. Thus, the sales management model is properly implemented by a company.